Education and Experience Drive MSME Financial Success Globally: Pendidikan dan Pengalaman Mendorong Kesuksesan Finansial UMKM Secara Global - Putri, Devy Amelia; Abidin, Fityan Izza Noor (Indonesian Journal of Education Methods Development, 2024)
This study examines the impact of education level, accounting knowledge, and business experience on the utilization of accounting information among MSME owners in Gempol, Pasuruan. Using a quantitative approach with 30 MSME owners as respondents selected through purposive sampling, data were collected via Likert scale questionnaires and analyzed using SPSS. Results indicate that education level and business experience significantly affect accounting information utilization, while accounting knowledge does not. These findings underscore the importance of considering education and experience in designing interventions to improve MSMEs' financial management practices, offering insights for policymakers and business support organizations aiming to enhance MSME growth and development in the region.Highlight: Education and experience influence accounting information utilization among MSME owners. Accounting knowledge has limited impact on information utilization. Findings inform policy for enhancing MSME financial management practices. Keyword: MSMEs, Accounting Information Utilization, Education Level, Business Experience, Gempol Pasuruan